MS_HistoneDB, a manually curated resource for proteomic analysis of human and mouse histones. Issue 1 (December 2017) - El Kennani, Sara; Adrait, Annie; Shaytan, Alexey; Khochbin, Saadi; Bruley, Christophe; Panchenko, Anna; Landsman, David; Pflieger, Delphine; Govin, Jérôme
Abstract Background Histones and histone variants are essential components of the nuclear chromatin. While mass spectrometry has opened a large window to their characterization and functional studies, their identification from proteomic data remains challenging. Indeed, the current interpretation of mass spectrometry data relies on public databases which are either not exhaustive (Swiss-Prot) or contain many redundant entries (UniProtKB or NCBI). Currently, no protein database is ideally suited for the analysis of histones and the complex array of mammalian histone variants. Results We propose two proteomics-oriented manually curated databases for mouse and human histone variants. We manually curated >1700 gene, transcript and protein entries to produce a non-redundant list of 83 mouse and 85 human histones. These entries were annotated in accordance with the current nomenclature and unified with the "HistoneDB2.0 with Variants" database. This resource is provided in a format that can be directly read by programs used for mass spectrometry data interpretation. In addition, it was used to interpret mass spectrometry data acquired on histones extracted from mouse testis. Several histone variants, which had so far only been inferred by homology or detected at the RNA level, were detected by mass spectrometry, confirming the existence of their protein form. Conclusions Mouse and human histone entries were collected from different databases and subsequently curated to produce a non-redundant protein-centric resource, MS_HistoneDB. It is dedicated to the proteomic study of histones in mouse and human and will hopefully facilitate the identification and functional study of histone variants.